DESIGN OF THE MEANINGFUL-MINDFUL-JOYFUL (M3J) LEARNING MODEL TO STRENGTHEN STUDENTS' 6CS COMPETENCIES IN THE INDONESIAN LANGUAGE COURSE - Hajar Nurma wachidah (Indonesian language and literature education program Majapahit Islamic University, 2026)
This study aims to design a conceptual learning model, referred to as Meaningful-Mindful-Joyful (M3J) Learning, intended to strengthen six core twenty-first-century competencies (6Cs: Character, Citizenship, Critical Thinking, Creativity, Collaboration, and Communication) among university students enrolled in the compulsory Indonesian Language course (Mata Kuliah Wajib Kurikulum/MKWK Bahasa Indonesia), which has tended to remain cognitive-mechanistic and superficially digitalized without addressing students' affective and reflective dimensions. The model was developed through a Research and Development (R&D) approach adopting the Plomp model, focusing on its initial investigation and design phases; needs analysis was conducted through literature review, classroom observation in three higher-education institutions, and in-depth interviews with Indonesian-language lecturers and students, followed by the conceptual formulation of three integrated pillars—meaningful (contextual-reflective), mindful (contemplative awareness), and joyful (a positive learning ecosystem)—mapped onto the 6Cs competency framework. The design process produced a theoretically grounded conceptual model that positions the affective-reflective dimension as an explicit component of Indonesian-language instruction, distinguishing it from prior innovative language-learning models confined largely to cognitive-instructional aspects; this conceptual model is proposed as the foundation for subsequent empirical validation, practicality testing, and effectiveness trials involving experimental and control groups of students enrolled in the Indonesian Language course. Keywords: M3J learning model; 6Cs competencies; deep learning approach; Indonesian language course.